Ben Yokoyama and the cookie of perfection - Swanson, Matthew, 1974- (Swanson, Matthew, 1974- Cookie chronicles, 2021)
After getting a fortune cookie with the message, "Practice makes perfect," Ben meets new student Darby, who claims to be perfect and offers to teach Ben his secrets.